QUALITY EVALUATION OF RESTRUCTURED-DEHYDRATED PRODUCT FROM FRESH WATER FISH - HANJABAM, MANDAKINI DEVI; KUMAR, ANUJ; KRISHNAMOORTHY, ELAVARASAN; C.S., TEJPAL; HANJABAM, HARIPYARI; CHANU, TONJAM KHUMANLEMBI; NINAN, GEORGE (Journal of the Inland Fisheries Society of India, 2026)
Restructured fish products are globally recognized for their unique texture and sensory attributes, but their high moisture content makes them highly perishable. This study focused on analyzing the quality of dehydrated, restructured fish products made from rohu (Labeo rohita) and their acceptability as base materials for coated snacks. Two formulations were used to produce the restructured-dehydrated products: one without black gram flour, referred to as RDP (Rohu Dehydrated Product), and the other with black gram flour, referred to as RFDP (Rohu-Flour Dehydrated Product). The protein content in RDP and RFDP was found to be 36.51% and 32.50%, respectively. The fat content in the dehydrated rohu products ranged from 18.84% to 14.16%. The rehydration ratio for RDP ranged from 0.90 to 1.25, while for RFDP it ranged from 1.31 to 1.62. In both products, the rehydration ratio increased over time. SDS-PAGE analysis of the protein profile showed bands at 200 kDa, 45 kDa, and 55-45 kDa. Both products received an overall acceptability score above 7 (like-moderately) on a 9-point hedonic scale. The findings suggest that mince-based dehydrated fish products can serve as a convenient material for producing ready-to-fry snacks.